"Calidad de la carne del cerdo mestizo (Yorkshire vs landrace) bajo diferentes métodos y periodos de conservación, en el Cantón El Emplame, 2014". - Yépez Castro, Jordy Ricardo (2014)
This research was conducted in the village of El Empalme Guayas Province. With geographic coordinates: Latitude 1° 02'46 ", longitude 79 ° 38'01" and altitude 71 msnm. In the evaluation of meat in the macro and micro nutrients they did in the lab UTE Extension Santo Domingo de los Tsáchilas. Design was used in this investigation Completely Random factorial arrangement (A x B) time (0, 20, 40 and 60 days) conservation with 6 replicates per treatment (8 treatments) with, giving a total of 48 experimental units to remove the differences in average, the multiple range test of Tukey at 5% probability was used. 40 kg of pork were used. Each sample contained pork 200 grams. In the pH in dried salted beef had an average of 6.20, was acceptable at 60 days with a mean of 5.85. The moisture of the meat jerky outperformed average of 31,92%. Ash, fat and protein had higher averages with 10,51%, 16,10% and 35,95% respectively. In the macronutrients of pork preservation method for drying had a high percentage of phosphorus, potassium and calcium with an average of 0,57; 0,35 and 0,34% respectively, a high percentage of phosphorus, potassium and calcium in the control with averages of 0,58 was taken; 0,43 and 0,51%, but a higher percentage of magnesium after 60 days of storage with 0,12%. In micronutrients pork preservation method for drying presented better results in copper, iron and manganese average of 5,73; 5,01 and 42,40 ppm respectively; copper, iron, zinc and manganese the highest yield was observed after 60 days of storage with averages of 5,58; 51,82; 68,59 and 6,64 ppm. All samples meet the INEN RULES and economic analysis the dried pork posted a net profit of $ 11,60 per pound of meat.